NON-CENTRAL ROLLING OF FLAT WORKS WITH TAPERED THICKNESS - I. A. Isaevich; V. A. Korol; V. S. Karpitskij; M. I. Sidorenko; D. M. Ivanitskij (Литьë и металлургия)
The way of forming of variable shape strips with rolling in non-drive waves with rounding by the movable arbor strip is analyzed. The way of rolling with derivation of speeds of deforming instruments is offered.